Should I stay or should I go? Three-year-olds' reactions to appropriate motives to interrupt a joint activity - Bonalumi, Francesca; Siposova, Barbora; Christensen, Wayne; Michael, John (PLoS One, 2023)
Understanding when it is acceptable to interrupt a joint activity is an important part of understanding what cooperation entails. Philosophical analyses have suggested that we should release our partner from a joint activity anytime the activity conflicts with fulfilling a moral obligation. To probe young children's understanding of this aspect, we investigated whether 3-year-old children (N = 60) are sensitive to the legitimacy of motives (selfish condition vs. moral condition) leading agents to intentionally interrupt their joint activity. We measured whether children protested or released their partner by scoring their reactions. Our results indicate that children did not manifest different reactions when the motive behind their partner leaving was moral than when the motive was selfish. However, our data showed a stable pattern: regardless of the partner's motives, some 3-year-olds take initiatives to release their partners from joint activity, suggesting that measuring release is a valuable tool for investigating joint action.
Keywords: Moral Obligations; mravy; Morals; pud; Drive; motivace; Motivation; morální závazky